PENDEKATAN PEDAGOGIS DALAM STUDI ISLAM - Bayu Bambang Nurfauji; Ela Nurlaela; Fatma Nurul Aini; Santi Nurya Cahya Andini; Cici Ely Pratiwi (CV. ADIBA AISHA AMIRA, 2026)
Islamic Religious Education (PAI) faces significant challenges related to educational quality and teacher professionalism in the 21st century. This background underscores the importance of strengthening pedagogical foundations oriented towards Islamic prophetic values. The objective of this study is to examine the pedagogical foundations of PAI in schools. The method used is a qualitative literature study. The results indicate that the pedagogical foundations of PAI are derived from divine values (worship, ihsan, future orientation, mercy, trustworthiness, da'wah, tabsyir) and encompass four philosophical views of humans: as beings who can be educated and educate others, education as a lifelong process, education as a basic human need, and humans as religious beings. Its implementation applies collaborative approaches, Vygotsky's social constructivism, and teacher exemplarity (uswah hasanah) to holistically shape character. In the digital era, integrating technology as a value-laden pedagogical medium becomes a necessity. The conclusion emphasizes that pedagogical approaches based on Qur'anic values, Prophetic Sunnah, and modern educational theory serve as a strategic foundation for shaping a generation of Muslims who are knowledgeable, virtuous, critical, and capable of wisely adapting to contemporary challenges